Pre-operative Radiotherapy And Deep Inferior Epigastric Artery Perforator (DIEP) flAp study (PRADA): Aesthetic outcome and patient satisfaction at one year. (March 2023) - Godden, Amy R.; Micha, Aikaterini; O'Connell, Rachel L.; Mohammed, Kabir; Kirby, Anna M.; Thiruchelvam, Paul T.R.; Leff, Daniel R.; MacNeill, Fiona A.; Rusby, Jennifer E.; ,; Cleator, Susan; Godden, Amy; et al.
Summary: Introduction: The optimal combination of radiotherapy and breast reconstruction has not yet been defined. Post-mastectomy radiotherapy (PMRT) has deleterious effects on breast reconstruction, leading to caution amongst surgeons. Pre-operative radiotherapy (PRT) is a growing area of interest, is demonstrated to be safe, and spares autologous flaps from radiotherapy. This study evaluates the aesthetic outcome of PRT and deep inferior epigastric artery perforator (DIEP) flap reconstruction within the P re-operative R adiotherapy A nd D eep Inferior Epigastric artery Perforator (DIEP) flA p (PRADA) cohort. Methods: PRADA was an observational cohort study designed to evaluate the feasibility and safety of PRT for women undergoing neoadjuvant chemotherapy and DIEP reconstruction. Panel evaluation of 3D surface images (3D-SIs) and patient-reported outcome measures (BREAST-Q) for a subset of women in the study were compared with those of a DIEP-PMRT cohort who had undergone DIEP reconstruction and PMRT. Results: Seventeen out of 33 women from the PRADA study participated in this planned substudy. Twenty-eight women formed the DIEP-PMRT cohort (median follow-up 23 months). The median (inter-quartile range [IQR]) 'satisfaction with breasts' score at 12 months for the PRADA cohort was significantly better than the DIEP-PMRT cohort (77 [72-87] versus 64 [54-71], respectively), p=0.01 ). Median [IQR] panel evaluation (5-point scale) was also significantly better for the PRADA cohort than for the DIEP-PMRT cohort (4.3 [3.9-4.6] versus 3.6 [2.8-4] p=0.003 ). Conclusions: Aesthetic outcome for the PRADA cohort was reported to be 'good' or 'excellent' in 93% of cases using a bespoke panel assessment with robust methodology. Patient satisfaction at one year is encouraging and superior to DIEP-PMRT at 23 months. Switching surgery-radiotherapy sequencing leads to similar breast aesthetic outcomes and warrants further large-scale, multi-centre evaluation in a randomised trial.